2018
DOI: 10.1016/j.apsusc.2017.09.044
|View full text |Cite
|
Sign up to set email alerts
|

Rapid formation of nanostructures in Au films using a CO2 laser

Abstract: We systematically investigate the formation of nanostructures in magnetron-sputtered Au films using a CO2 laser. By comparing the optical properties and surface morphologies of Au films on different kinds of substrates before and after laser irradiation with different laser powers and irradiation times, we find that the nanostructures are most rapidly formed in the Au film with 5 nm thickness on a thin glass substrate. With the laser power of 6 W and a beam diameter of ~10 mm at the Au film, only a few tens of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…To ensure the maximum absorption of laser energy by the glass substrate the laser is irradiated from the back side (i.e., glass side) of the film. In reality, however, whether the CO 2 laser is irradiated from the front or back side of the film does not matter if the film thickness is 5 nm, but it matters if it is beyond ∼7 nm [29]. The temperature of the Ag film during laser irradiation is measured using a thermocouple with a size of ∼1 mm.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To ensure the maximum absorption of laser energy by the glass substrate the laser is irradiated from the back side (i.e., glass side) of the film. In reality, however, whether the CO 2 laser is irradiated from the front or back side of the film does not matter if the film thickness is 5 nm, but it matters if it is beyond ∼7 nm [29]. The temperature of the Ag film during laser irradiation is measured using a thermocouple with a size of ∼1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Recently a focused CO 2 laser beam has been employed to induce nanostructures in thin films [27,28]. More recently we have demonstrated that the irradiation of a non-focused CO 2 laser beam with a power density of 4∼6 W/cm 2 to a 5 nm Au film on a glass substrate for several seconds is sufficient to induce Au nanostructures [29]. Knowing that CO 2 laser annealing of thin Au films works well, how it works for thin Ag films is an interesting question, since they are also frequently used for many applications.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The feasibility of pulsed laser-induced dewetting, especially using nanosecond pulses, has attracted significant attention in the literature [24][25][26][27][28][29][30]. However, only scant information is available regarding the synthesis of metallic NPs using a high repetition rate laser.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of pulsed laser-induced dewetting, especially that using nanosecond pulses, has attracted significant attention in the literature [24][25][26][27] . However, only scant information is available regarding the synthesis of metallic NPs using a high repetition rate laser.…”
Section: Introductionmentioning
confidence: 99%